The Influence of Motivation and Work Environment towards Employee Performance in the Marketing Division PT. United Motors Center Suzuki Surabaya - Rangga, Marendra Krisdya; Santoso, Bowo (Budapest International Research and Critics University, 2021)
Employee performance is the result of work both quantity and quality produced by employees or real behavior that is displayed in accordance with the duties and responsibilities assigned to him. This study aims to determine the importance of motivation and work environment on employee performance in the marketing division of PT. united motors center suzuki surabaya. The population used in this study was a total of 110 employees. The sample used is a saturated sample, that is, all members of the population are used as samples. The data analysis technique used in this research is the partial least squares (PLS) analysis method. Based on the results of the research conducted, it can be concluded that motivation contributes to employee performance and the work environment contributes to employee performance.